CHARACTERISTICS OF EXTERNAL FACTORS WHAT INFLUENCE THE PHYSICAL SELF-EDUCATION OF FUTURE ENGINEERS-TEACHERS - V.O. Pavlenko (Academy of Cognitive and Natural Sciences, 2010)
In the article external factors are grounded and described in theory. This factors in fluence physical self-education of future engineers-teachers in the process of organization them professionally preparations in higher educational establishment.